Signaling pathway of vitamin D, vitamin D receptor and autophagy in infection: a systematic review - Sartika, Katarina Dewi; Gayatri, Anak Agung Ayu Yuli (International Journal of Advances in Medicine, 2022)
Vitamin D has an immunomodulatory effect that increases antimicrobial responses in macrophages by inducing antibacterial proteins, stimulating autophagy, and increasing autophagosome activity through various signaling pathway. This review emphasizes the several signalling pathway of vitamin D and vitamin D receptor (VDR) to induce autophagy in infection and its role in infectious disease. This study was performed based on PRISMA guidelines. Literature search conducted from Cochrane, PubMed, Science Direct and ProQuest using the terms "vitamin D" and “VDR” and "autophagy in infection". The inclusion criteria were original article, publication in English, published in 2012-2022, investigating vit D, VDR pathway and autophagy mechanism in infection. Twelves studies met our criteria. Despite numerous autophagy signalling in vitamin D and VDR, there are 2 main mechanisms vit D induces autophagy; increase expression LL-37/cathelicidin, CAMP, DEFB4 and upregulated autophagy genes (LC3B, ATG5, BECN1, MMPI, ATG16L1, PR39). While, vit D induced autophagy via expression CYP27B1 and VDR in co-infection HIV and tuberculosis. In sepsis, artesunate relates with VDR to enhance autophagy via NF-κB. Similarly, vitamin D could enhance cell resistance to Aspergillus fumigatus after modulating NF-κB. Vitamin D3 through PDIA3-STAT3-MCOLN3-Ca2+ axis and CAMP/LL-37 (cathelicidin antimicrobial peptide) are mediator for autophagy induction in H. pylori. Upregulated autophagy gene activity through vit D/VDR appears as new target therapy for infection in future.